2007
DOI: 10.1021/ac0709192
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of DNA Copy Number in Individual Mitochondrial Particles by Capillary Electrophoresis

Abstract: Here, we present a direct method for determining mitochondrial DNA (mtDNA) copy numbers in individual mitochondrial particles, isolated from cultured cells, by means of capillary electrophoresis with laser-induced fluorescence (CE-LIF) detection. We demonstrate that this method can detect a single molecule of PicoGreen-stained mtDNA in intact DsRed2-labeled mitochondrial particles isolated from human osteosarcoma 143B cells. This ultimate limit of mtDNA detection made it possible to confirm that an individual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 50 publications
3
29
0
Order By: Relevance
“…Although we have not determined numbers of mtDNAs within individual nucleoids, the distribution of our volumetric data is Fig. 5A is remarkably similar to typical distributions of mtDNAs per nucleoid described by others (11,42,54). This correlation is substantiated by the conversion of volumes to genomes.…”
Section: Discussionsupporting
confidence: 84%
“…Although we have not determined numbers of mtDNAs within individual nucleoids, the distribution of our volumetric data is Fig. 5A is remarkably similar to typical distributions of mtDNAs per nucleoid described by others (11,42,54). This correlation is substantiated by the conversion of volumes to genomes.…”
Section: Discussionsupporting
confidence: 84%
“…While we find no association between mtDNA content and embryonic stress, our data does not refute the proposed concept that embryos actively increase mitochondrial function and energy output as a compensatory response to overcome strained conditions. The number of mtDNA copies per mitochondrion in human cells can vary widely between 0 to 15 (21)(22)(23), meaning that the number of mtDNA copies per cell does not necessarily correlate to number of mitochondrial organelles. At least one report has demonstrated that mtDNA copy is a poor biomarker for mitochondrial content (24).…”
Section: Discussionmentioning
confidence: 99%
“…Lower pH values were determined in the acidic organelles of drug-resistant cell lines. Another report described the absolute quantitation of mitochondrial DNA (mtDNA) copy number in individual mitochondrial particles (152). Mitochondria isolated from cells expressing mito-DsRed2 (i.e., mitochondria label) were treated with a DNA intercalator (i.e., PicoGreen) and then analyzed by CE with a dual LIF detector.…”
Section: Bioparticlesmentioning
confidence: 99%